Does human cytomegalovirus provide a novel therapeutic target for patients with glioblastoma? - Söderberg-Naucler, Cecilia; Pantalone, Mattia R.; Stragliotto, Giuseppe; Bartek, Jiri (The Royal Society, 2026)
Glioblastoma is the most common and aggressive primary malignant brain tumour in adults, with limited treatment options despite years of research. Since the 2005 introduction of the current standard of care, hundreds of clinical trials have failed to deliver significant breakthroughs. In 2002, human cytomegalovirus (HCMV) was detected in 100% of glioblastoma tumours. Although its role in cancer remains debated, and HCMV is not classified as an oncovirus, numerous studies have reported high viral prevalence in glioblastoma. HCMV can induce all 10 'hallmarks of cancer' and has been shown to modify both tumour cell behaviour and the microenvironment, which may enhance tumour growth and promote immune evasion. The association between HCMV and poor glioblastoma prognosis has generated increasing interest in targeting the virus therapeutically. Our clinical studies suggest that adding antiviral treatment to standard care may improve survival in both primary and recurrent glioblastoma. Moreover, an mRNA-based HCMV pp65 dendritic cell vaccine has shown preliminary indications of a potential survival benefit in early phase studies. Future research should prioritize clarifying HCMV's role in glioblastoma and rigorously evaluating antiviral and immunotherapeutic strategies in randomized clinical trials.This article is part of the theme issue 'The indirect effects of cytomegalovirus infection: mechanisms and consequences'.